Application of KNN algorithm in classification of agricultural products - Đỗ Văn Cần; Bùi Văn Vũ; Nguyễn Đức Thịnh (My University, 2022)
Application of KNN algorithm in classification of agricultural products
Keywords: Thuật toán KNN; Phân loại nông sản; Trí tuệ nhân tạo